STUDI PARADIGMA NARATIF WALTER FISHER PADA AKTIVITAS â€œNONGKRONGâ€ DI KALANGAN REMAJA MADYA - Glorya Agustiningsih (Jurnal Komunikasi dan Bisnis, 2013)
Adolescents and the activity of "hanging out" are two things that very attached now. Even, the activity of "hanging out" also affect the formation of self identity middle adolescents. When they doing the activity of â€œhanging outâ€ and share story, their peers could be influence either positive or negative. If the influence obtained a positive, then the adolescent can form a positive self identity as well. However, if peers gave a negative influence, then the adolescent can experience an identity crisis and fall into the negative things. Therefore, the author interested to lift research topic about a description of the narrative paradigm among the middle adolescents in the activity of â€œhanging outâ€, in order to know the mindset of the middle adolescents in filtering a story.The results of this thesis research shows that middle adolescents who became the subject of a research has a mindset that is positive. Where it can be seen from the answers to the subject which makes the content of positive values in the story as an indicator of a story that makes sense and reason in choosing a good story.Conclusion in this research is family and school environment are environments that greatly influences the mindset of the middle adolescents. It was because ranging from family, adolescents gain a positive guidance and input, and can filter the influence gained from social environment in which they grew up. In the school environment, a lot of adolescents get together and hang out with their peers who have backgrounds as well as a different mindset.Â Keyword: Hanging Out, Adolescent, Narrative, Walter Fisher